A Study On Factors That Influence Consumers' Purchasing Pattern And Decision Making On Life Insurance Product In Malaysia - Suu, Mei Lean (2007)
There are notmuch research done in Malaysia regarding factors influencing consumers' purchasing pattern and decision making on life insurance products. Therefore, this research is conducted to justify some of the factors and to study the empirical evidence in terms of services, income, education level, economic development, social attribute, marketing strategies, culture and role of the agents in Selangor and Malacca.